Hypothalamic–Pituitary–Thyroid Axis Crosstalk With the Hypothalamic–Pituitary–Gonadal Axis and Metabolic Regulation in the Eurasian Tree Sparrow During Mating and Non-mating Periods - Nabi, Ghulam; Hao, Yinchao; Liu, Xuelu; Sun, Yanfeng; Wang, Yang; Jiang, Chuan; Li, Juyong; Wu, Yuefeng; Li, Dongming (Frontiers in Endocrinology, 2020)
Reproduction is an energetically costly phenomenon. Therefore, to optimize reproductive success, male birds invest enough energetic resources for maintaining well-developed testes. The hypothalamic-pituitary-thyroid (HPT) axis in birds can crosstalk with the hypothalamic-pituitary-gonadal (HPG) axis, thus orchestrate both the reproduction and metabolism. However, until now, how the free-living birds timely optimize both the energy metabolism and reproduction via HPT-axis is not understood. To uncover this physiological mechanism, we investigated the relationships among body mass, testis size, plasma hormones including thyroid-stimulating hormone (TSH), thyroxine (T4), triiodothyronine (T3), metabolites including glucose (Glu), triglyceride (TG), total cholesterol (TC), and uric acid (UA), diencephalon mRNA expressions of type 2 (Dio2) and 3 (Dio3) iodothyronine deiodinase enzymes, thyrotropin-releasing hormone (TRH), thyroid-stimulating hormone (TSH), gonadotropin-releasing hormone I (GnRH‐I), and gonadotropin-inhibitory hormone (GnIH) in a male Eurasian tree sparrow (ETS, Passer montanus). We found significantly larger testis size, elevated diencephalon Dio2 and TRH mRNA expressions, plasma T3 and UA levels, and significantly lowered Glu, TG, and TC levels during mating relative to the non-mating stages in male ETSs. However, Dio3, TSH, GnRH‐I, and GnIH mRNA expression did not vary with the stage. Furthermore, life-history stage dependent variation in plasma T3 had both direct effects on the available energy substrates and indirect effects on body mass and testis size, indicating a complex regulation of metabolic pathways through the HPT and HPG-axes. The identified differences and relationships in mRNA expression, plasma T3 and metabolites, and testis size in male ETSs contribute to our understanding how free-living birds adjust their molecular, endocrine , and biochemical features to orchestrate their reproductive physiology and metabolism for the maintenance of well-developed testes.